Design and evaluation of a sensor network for medical monitoring in areas of difficult access - Castillo Quiel, Yarisol; Saavedra, Amilkar; Villarreal, Vladimir (Ingeniería Solidaria, 2020)
Introduction: This article is the result of the research "Framework for the implementation of IPv6 using 6LoWPAN in sensor networks to facilitate the monitoring and control of people with dependency needs" developed at the Universidad Tecnológica de Panamá in the year 2019-2020.Problem: The medical care of patients in rural areas of Panama is a priority, they need a constant follow-up and monitoring of their illness, there is no system that allows medical personnel to keep a continuous control.Objective: The research proposes the development of a system with electronic devices using low power networks, which allows patients to send their clinical data to a central server, storing them and later a doctor can make an evaluation of the disease to keep a control, follow up and monitoring of the patients that reside in areas of difficult access.Methodology: For the design and progressive development of the system, the use of the incremental methodology is proposed.Results: Once developed both the hardware and the software, we tested the model in different scenarios recording measurements for pulse at different distances.Conclusion: The implementation of a low-cost system offers the possibility to patients, who do not have access to regular health services, to have a better control and recommendations from the doctor.Originality: Some similar systems have been developed, but not all of them contemplate security aspects for the handling of sensitive and delicate data.Limitations: The maximum distance allowed is 60 meters at the time of testing the data.
Keywords: 6LoWPAN (IPv6 over Low power Wireless Personal Area Networks); ipv6 (Internet Protocol version 6); WSN (Wireless sensor networks); sensors